2021
DOI: 10.3390/brainsci11111477
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Factors Linking Insecure Attachment to Psychopathology: A Systematic Review

Abstract: Although many studies have documented associations between insecure attachment and psychopathology, attachment may not confer risk for psychopathology independently, but rather through its interaction with emotional, social, and biological factors. Understanding the variables through which attachment may lead to psychopathology is therefore important. Within this domain of research, the role of physiological factors is poorly investigated. What are the relevant domains and why, when, or for whom do they influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 141 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…Regarding dismissal, some authors (Mikulincer & Shaver, 2012; Rosenstein & Horowitz, 1996) highlight dismissal as more related to substance use disorders and narcissistic traits in adolescents, of which symptoms not captured by the YSR and CBCL internalizing and externalizing problems scales considered in this study. Concerning disorganization, a recent systematic review (Tironi et al, 2021) highlights that, in general, insecure attachment and particularly disorganization are more related to psychophysiological vulnerabilities predisposing to psychopathologies—such as emotional dysregulation and overreactive response to stressors—than being related directly to a certain type of symptoms. In this regard, one can also hypothesize more complex pathways of relationships among these constructs, which may be part of a broad framework where adolescents' symptomatology and difficulties in the area of emotional regulation co‐occur as sides of the same vulnerability coin (Aldao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dismissal, some authors (Mikulincer & Shaver, 2012; Rosenstein & Horowitz, 1996) highlight dismissal as more related to substance use disorders and narcissistic traits in adolescents, of which symptoms not captured by the YSR and CBCL internalizing and externalizing problems scales considered in this study. Concerning disorganization, a recent systematic review (Tironi et al, 2021) highlights that, in general, insecure attachment and particularly disorganization are more related to psychophysiological vulnerabilities predisposing to psychopathologies—such as emotional dysregulation and overreactive response to stressors—than being related directly to a certain type of symptoms. In this regard, one can also hypothesize more complex pathways of relationships among these constructs, which may be part of a broad framework where adolescents' symptomatology and difficulties in the area of emotional regulation co‐occur as sides of the same vulnerability coin (Aldao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that attachment-related avoidance and attachment-related anxiety are associated with heightened stress experiences. Furthermore, evidence from an experimental setting ( Ehrenthal et al, 2018 ) has demonstrated that attachment insecurity in adults can act as a moderator between adverse experiences and physiological stress response, suggesting that attachment representations may have a life-long stress-regulating effect ( Tironi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence suggesting that attachment patterns play an important role in the development of emotional dysregulation, a concept that is involved in the development of all three disorders (21,22). The association between attachment and risk factors for psychiatric disorders, such as emotional dysregulation, seems to be clearer than the association between insecure attachment and speci c disorders (23). Some studies suggest that insecure attachment plays a role in mediating the development of borderline features, but temporal causality has not been established (24)(25)(26).…”
mentioning
confidence: 99%